2008
DOI: 10.1029/2008gl036146
|View full text |Cite
|
Sign up to set email alerts
|

COSMIC/FORMOSAT‐3 tomography of SEP ionization in the polar cap

Abstract: We studied ionization effects produced by solar energetic particles (SEP) in the northern polar ionosphere and atmosphere during December 2006 (local night). Height profiles of specific ionization produced by the SEP in the polar cap were calculated using POES data on energetic particles. The SEP ionization dynamics reveals three intensifications at heights from 50 to 100 km in 7 to 8, 13 and 14 December. At the same time a 3‐D tomography of electron content (EC) in the ionosphere and upper atmosphere was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The following major storms have attracted attention to date because they resulted in a specific thermosphere‐ionosphere‐magnetosphere system response: the July event [ Burke et al ., ; Kunitsyn et al ., ; Lazutin , ; Li et al ., ; Ngwira et al ., ; Pedatella et al ., ; Stephan et al ., ]; the November event [ Fejer et al ., ; Paznukhov et al ., ; Balan et al ., , ; Huang , ; Mannucci et al ., ; Deng et al ., ; Sahai et al ., ; Kelley et al ., ; Solovyev et al ., ; Abdu , ] (special issue of Journal of Atmospheric and Solar-Terrestrial Physics , 2010) and the December event [ Lei et al ., , ; Dmitriev et al ., , ; Pedatella et al ., ; de Jesus et al ., ; Klimenko and Klimenko , ; Wei et al ., ; Suvorova et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following major storms have attracted attention to date because they resulted in a specific thermosphere‐ionosphere‐magnetosphere system response: the July event [ Burke et al ., ; Kunitsyn et al ., ; Lazutin , ; Li et al ., ; Ngwira et al ., ; Pedatella et al ., ; Stephan et al ., ]; the November event [ Fejer et al ., ; Paznukhov et al ., ; Balan et al ., , ; Huang , ; Mannucci et al ., ; Deng et al ., ; Sahai et al ., ; Kelley et al ., ; Solovyev et al ., ; Abdu , ] (special issue of Journal of Atmospheric and Solar-Terrestrial Physics , 2010) and the December event [ Lei et al ., , ; Dmitriev et al ., , ; Pedatella et al ., ; de Jesus et al ., ; Klimenko and Klimenko , ; Wei et al ., ; Suvorova et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the specific ionization of electrons (the energy loss per unit distance) and the standard vertical profile of the upper atmosphere [e.g., Dmitriev et al ., ], we were able calculate the number of bounces between the top point at 800 km and the mirror points at a height of H min until the ~30 keV electron lost its energy in ionization. In this manner, we found that for a H min below 600 km, ~30 keV electrons lose their energy within ~2 h. During this time period, electrons pass eastward no more than ~30° in longitude because of a very slow azimuthal drift.…”
Section: Quasi‐trapped Electron Impacts and Uncertainties In Tec Estimentioning
confidence: 99%
“…Note that there were no FEE enhancements at that time. At high latitudes, the ionizing effect of the solar energetic electrons was a main source of the enhanced VTEC [ Dmitriev et al , , ]. At middle latitudes (40°–50°) in the noon sector, the localized increase of VTEC was likely caused by electrons precipitating from the radiation belt due to strong compression of the dayside magnetosphere (Figure , left).…”
Section: Discussionmentioning
confidence: 99%
“…On 14 December 2006, the ionosphere was strongly disturbed by solar energetic particles and transient geomagnetic storm. During the day, the solar energetic particles caused intense ionization of the bottomside ionosphere in the polar cap [ Dmitriev et al , , ], while a storm‐associated increase of ionization was observed in the topside ionosphere at lower latitudes [e.g., Suvorova et al , ]. The storm began after a sudden commencement at ~1400 UT followed by a long initial phase lasting until ~2230 UT.…”
Section: Positive Ionospheric Storm At the Initial Phasementioning
confidence: 99%
See 1 more Smart Citation